Perineal stapled prolapse resection for full‐thickness external rectal prolapse: a multicentre prospective study. (3rd November 2016) - Mistrangelo, M.; Tonello, P.; Brachet Contul, R.; Arnone, G.; Passera, R.; Grasso, L.; Rapetti, L.; Borroni, R.; Pozzo, M.; Roveroni, M.; Morino, M.; Perinotti, R.
Abstract: Aim: Many different surgical techniques have been reported for the surgical treatment of full‐thickness external rectal prolapse. Perianal stapled prolapse resection (PSP) is a relatively newly reported technique for full thickness external rectal prolapse. The aim of this prospective multicentre study was to evaluate the results of this procedure. Method: Consecutive patients who underwent a PSP resection for full‐thickness external rectal prolapse at five centres were recruited to the study. Median operating time, hospital stay, complications, recurrence and functional results according to the Wexner Incontinence Scale and obstructive defaecation syndrome score were recorded. Results: There were 27 patients treated by PSP. The median Wexner incontinence score improved from 10 presurgery to 5 after surgery ( P  < 0.001); the median obstructed defaecation syndrome score improved from 12 presurgery to 5 (range 4–10) after surgery ( P  < 0.001). A laparoscopically assisted procedure was performed in three patients (11.1%). The median number of cartridges used was six (range four to nine). The median operating time was 48 min. Early complications occurred in six patients (22.2%) and late complications in two (7.4%). The median length of hospital stay was 5 days. The recurrence rate at a median follow‐up of 30.3 months was 14.8%. Conclusion: PSP appears to be an easy, fast and safe procedure. Early functional results are good. The recurrence rate compares favourably with other perineal procedures like the Delorme or the Altemeier operations. Long‐term functional results need to be investigated further.